Teff (Eragrostis tef Zucc) yield response to NPSB blend and KCl fertilizer application on Planosols - Biratu, Gizachew Kebede; Elias, Eyasu; Berecha, Gezahegn; Mamuye, Melkamu (Taylor and Francis Ltd., 2025)
Planosols cover extensive areas in the south-western highlands of Ethiopia. This study reports the effect of different rates of NPS and its potassium and boron blend on teff yield. Eight treatments: no application (T1), 100 NPS (T2), 200 NPS (T3), 300 NPS (T4), 100 NPS + 50 KCl (T5), 200 NPS + 100 KCl (T6), 300 NPS + 150 KCl (T7), and 100 NPSB kg/ha (T8) were arranged in a randomized complete block design (RCBD) and replicated four times. The result revealed that the application of NPS fertilizer significantly improved both teff grain and straw yield , but the inclusion of K and B did not. While the inclusion of B significantly increased agronomic efficiency of S, economic analysis showed that all the treatments were with BCR greater than one. The highest NB(37,968.1 Birr/ha) was obtained from T7 and the highest MRR(14671.5%) was from T8. There was no significant yield advantage and the economic return from the inclusion of K in the blends. We recommend 100 kg/ha NPSB for teff production on Planosols. As there is no significant yield advantage and low economic incentive from the inclusion of KCl in the blend, K should be removed from the blend fertilizer formulation.